CARBON ISOTOPE RECORD FOR THE ONSET OF THE LOMAGUNDI CARBON ISOTOPE EXCURSION IN THE GREAT LAKES AREA, NORTH AMERICA - Bekker A.; Karhu J.A.; Kaufman A.J. (My University, 2006)
Carbonate units of the Chocolay Group in the Lake Superior area, USA and the Gordon Lake Formation of the correlative upper Huronian Supergroup, Ontario, Canada were deposited after the last Paleoproterozoic glacial event and an episode of intense chemical weathering. The Huronian Supergroup contains at the base ~2.45 Ga volcanics and is intruded by the 2.22 Ga Nipissing diabase dykes and sills while the Chocolay Group is bracketed in age between ~2.29 and 2.20 Ga. The Lomagundi (~2.22-2.1 Ga) carbon isotope excursion started after the Paleoproterozoic glacial epoch and before a plume breakout event at 2.22 Ga. Therefore, the Chocolay and Upper Huronian carbonates were deposited either before or during the onset of the Lomagundi event. Notably, thin carbonates of the basal Gordon Lake Formation and thick carbonate succession of the Kona Dolomite in the northeastern exposures of the Chocolay Group record δ13C values as high as +9.5‰ versus V-PDB. Similar to other successions deposited during the Lomagundi event, both units contain pseudomorphs and molds after sulfates. This observation suggests that seawater sulfate contents rose dramatically in association with the onset of the Lomagundi event and the rise of atmospheric oxygen. Carbonates in the western and southern exposures of the Chocolay Group (Randville and Bad River dolomites, and Saunders Formation) previously assumed to be equivalent to the Gordon Lake Formation and Kona Dolomite have carbon isotope values close to 0‰. Based on basin analysis, we infer that these carbonate units were deposited during a negative carbon isotope excursion after the Lomagundi event started and are slightly younger than the Kona Dolomite and Gordon Lake Formation. This interpretation implies that the carbonate platform in the Great Lakes area transgressed to the west over shallow-marine and fluvial deposits. The negative carbon isotope excursion in the Lake Superior area might correspond to similar δ13C values of the Mooidraai Dolomite in the Griqualand West Basin, South Africa supporting correlation between Paleoproterozoic successions of North America and South Africa and the notion of three global glaciations in the Paleoproterozoic Era. Carbonates of the Mille Lacs Group (Trout Lake, Glen Township, and Denham formations) in Minnesota have δ13C values ranging from -1.2 to +2.5‰. Combined with geochronologic constraints, these data suggest that these units were deposited after the Lomagundi excursion and are related to the rifting event that led to development of the so far unrecognized ~2.0 Ga passive margin in the Lake Superior area. © 2006 Elsevier B.V. All rights reserved.
Keywords: BASIN ANALYSIS; CHEMOSTRATIGRAPHY; CHOCOLAY GROUP; GLACIATION; HURONIAN SUPERGROUP; PALEOPROTEROZOIC ERA; Paleoproterozoic; Precambrian::Proterozoic::Paleoproterozoic; Докембрий::Протерозой::Палеопротерозойская